PEMANFAATAN ASAP CAIR LIMBAH SERABUT DAN TEMPURUNG KELAPA SEBAGAI PESTISIDA ORGANIK DI DUSUN MAKMUR DESA SUNGAI KUPAH - Imansyah, Fitri (Jurnal Abdi Insani, 2024)
Organic farming is increasingly recognized as a more environmentally friendly alternative to meet global food needs. However, the challenge of controlling pests and plant diseases without using chemical pesticides remains a problem that needs to be overcome. In carrying out this community service activity, introducing an innovative local solution through the use of liquid smoke from coconut fiber and shell waste as an organic pesticide in Makmur Hamlet, Sungai Kupah Village. The activity method involves collecting coconut fiber and shell waste from local industries, followed by the process of making liquid smoke through a simple pyrolysis technique. Furthermore, tests on the effectiveness of this liquid smoke were carried out on a small scale on vegetable and rice plants in the area. The results of the activity show that the application of coconut waste liquid smoke is able to control a number of pests and plant diseases effectively, while maintaining soil quality and healthy plants. Apart from agricultural benefits, this activity also has a positive economic impact by producing value-added products from coconut waste and supporting the sustainability of local industry. Apart from direct benefits in agriculture, the use of liquid smoke also has a positive impact on the environment and local economy by reducing unutilized coconut waste and reducing dependence on chemical pesticides. In conclusion, the use of coconut fiber and shell waste liquid smoke offers an innovative and sustainable solution for clean agriculture in rural areas such as Dusun Makmur, Sungai Kupah Village, while moving the direction towards more sustainable agriculture globally.